Observation of cardiac profile among the adult population of Sreemangal - Rafat, M. Nazem Al Qureshee; Anisuzzaman, A. H. M.; Das, Niloy Chandra; Roy, Arpita; Al Mamun, Abdullah; Anwarul Amin, M.; Hasan Ali, M.; Tahite, Dihan (International Journal of Research in Medical Sciences, 2024)
Background: Cardiovascular diseases are a leading cause of morbidity and mortality worldwide. The prevalence and risk factors of CVDs vary across different populations and regions. This study aimed to observe the cardiac profile among the adult population of Sreemangal, Bangladesh, to identify the prevalence and risk factors of CVDs in this population. Methods: This prospective observational study was conducted over a six-month period at a public health camp in Sreemangal, Bangladesh. A total of 137 adult participants were purposively selected. Data were collected through a structured questionnaire and physical examination, including measurements of blood pressure and laboratory analysis of blood samples. Results: The study found that 44.53% of participants had elevated blood pressure, and 21.90% had stage 1 hypertension. Interestingly, 36.50% of participants were unaware of their hypertension status. Furthermore, 26.28% of participants had a known history of diabetes, but blood glucose level analysis revealed an additional 14.85% of participants were prediabetic, and 6.93% were diabetic based on fasting blood glucose levels. A statistically significant association was found between increasing age and the stage of hypertension (p<0.001), and between fasting and normal blood glucose levels and the stage of hypertension (p<0.005 and p<0.05, respectively). Conclusions: The findings of this study underscore the need for targeted interventions to prevent and manage CVDs in the adult population of Sreemangal, Bangladesh. These interventions should include regular screening for CVD risk factors, health education to increase awareness of these risk factors, and strategies to promote healthy lifestyle behaviors.